2021
DOI: 10.1002/dc.24761
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphometry and morphology analysis of human papillomavirus type 16 in liquid‐based cervical cytology samples

Abstract: BackgroundHuman papillomavirus (HPV) is the main causal factor of cervical carcinoma. HPV 16 is one of the most prominent oncogenic types. We aimed to evaluate the cytomorphometric and morphological alterations caused by HPV 16 in liquid‐based cytology (LBC).MethodsThe Cobas 4800 HPV system was used for the detecting and typing HPV DNA in cervical specimens. In this study, 30 HPV 16 positive and 30 HPV 16 negative cervical samples were evaluated for micronuclei (MN), nonclassical cytologic abnormalities, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Safi Oz et al 1 presented quite interesting data concerning cytomorphology of cervical cells of women infected with papillomavirus type 16. They showed that viral infection increases frequencies of (i) koilocytotic cell (squamous epithelial cells with perinuclear cavitation and nuclear features of low-grade squamous intraepithelial lesions [LSIL]), (ii) cells with perinuclear halo (a vacuolated area that surrounds the nucleus), (iii) cells with micronuclei (MN).…”
mentioning
confidence: 99%
“…Safi Oz et al 1 presented quite interesting data concerning cytomorphology of cervical cells of women infected with papillomavirus type 16. They showed that viral infection increases frequencies of (i) koilocytotic cell (squamous epithelial cells with perinuclear cavitation and nuclear features of low-grade squamous intraepithelial lesions [LSIL]), (ii) cells with perinuclear halo (a vacuolated area that surrounds the nucleus), (iii) cells with micronuclei (MN).…”
mentioning
confidence: 99%
“…To the editor, I read the recent paper accepted for publication in the Diagnostic Cytopathology titled "Cytomorphometry and morphology analysis of human papillomavirus type 16 in liquid-based cervical cytology samples" by Safi Oz et al 1 with much interest. In the manuscript, the authors have demonstrated a high number of micronucleated cells in cervical exfoliated cells of patients infected with human papillomavirus 16 (HPV-16).…”
mentioning
confidence: 99%